2020
DOI: 10.1186/s13690-020-00516-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of antenatal care utilization among women of reproductive age in sub-Saharan Africa: evidence from multinomial analysis of demographic and health surveys (2010–2018) from 31 countries

Abstract: Background Despite a global reduction of about 38% in maternal mortality rate between 2000 and 2017, sub-Saharan Africa is still experiencing high mortality among women. Access to high quality care before, during and after childbirth has been described as one of the effective means of reducing such mortality. In the sub-region, only 52% of women receive at least four antenatal visits. This study examined the factors influencing antenatal care utilization in sub-Saharan Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
64
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 42 publications
19
64
2
Order By: Relevance
“…17 23 33 35 Compared with housewives, the number of ANC uptake was higher among employed women. This finding is similar to a study in Kenya 42 and 31 sub-Saharan Africa countries 43 which showed that the odds of ANC utilisation were higher among working women than non-working. 43 This may be because employed women, especially those in the formal sector, get benefit from a pregnancy care health insurance system.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…17 23 33 35 Compared with housewives, the number of ANC uptake was higher among employed women. This finding is similar to a study in Kenya 42 and 31 sub-Saharan Africa countries 43 which showed that the odds of ANC utilisation were higher among working women than non-working. 43 This may be because employed women, especially those in the formal sector, get benefit from a pregnancy care health insurance system.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to a study in Kenya 42 and 31 sub-Saharan Africa countries 43 which showed that the odds of ANC utilisation were higher among working women than non-working. 43 This may be because employed women, especially those in the formal sector, get benefit from a pregnancy care health insurance system. The finding indicated that women with pregnancy complications tend to uptake ANC service than those who did not develop pregnancy complications.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the increase in utilization of ANC in Ethiopia, the finding is less than the Ayder-Mekelle (88.9%), South African (78.1%), and Zimbabwe (76.2%) ANC utilization which showed there is still a big room for improvement (18,21,22). As evidence by 30.1% utilization in the Somali and 97.8% in Addis, disparities among the regions are very significant.…”
Section: Discussionmentioning
confidence: 88%
“…According to the existing kinds of literature, the plan is far from its achievement as there is no study ever presented with such information. The ANC distribution in the country was: ANC 1-3 (45.71%) and ≥4 ANCs(54.29%) from EDHS 2016(11); 62.8% overall ANC utilization from EDHS 2016(12); 29.3% in the Northeast Ethiopia in 2016(4); 54% ANC in Tigray in 2013; 42.8% in 2014 in Ambo Town (13); 77.4% in Sidama Zone in South Nation Nationalities people's region (SNNPR) in 2011 (14); 72.6% in Gedeo zone in 2020(6); 78.5% ≥4 ANCs in Debre Berhan in 2019 (15); 66.3% of women not used ANC at first trimester and 22.3% had four and less ANC from EDHS 2011 (16); urban women use 34% more ANC than rural women (17); the average ANC between 2000 and 2017(36.2%) (18). This showed exactly the position of the country in achieving the plan.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the finding from the current study shows that there were lower odds of noncompliance among older pregnant women compared to young pregnant women. Association between women's age and ANC service utilization was reported in Nepal [ 44 ], India [ 45 ], and SSA countries [ 46 , 47 ]. This could be partly explained by lack of experience in pregnancy care among young pregnant women compared to older pregnant women [ 46 ].…”
Section: Discussionmentioning
confidence: 99%